Cover Feature: Ionic Liquids as Extractants for Nanoplastics (ChemSusChem 20/2020). Issue 20 (28th September 2020) - Elfgen, Roman; Gehrke, Sascha; Hollóczki, Oldamur
Abstract : The Cover Feature shows the interplay of polar, non‐polar, and ionic liquid solvents with a polyethylene nanoplastic particle, represented by cats interacting with woolen yarn. Through the solvent, the disentanglement of the nanoplastic and the extraction process can be tuned. More information can be found in the Full Paper by R. Elfgen et al .